2020
DOI: 10.1101/2019.12.28.19016048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Preoperative Estimate of Central Venous Pressure Is Associated with Early Fontan Failure

Abstract: Objective Early Fontan Failure (EFF) is a serious complication following total cavopulmonary connection (TCPC), characterised by high central venous pressure (CVP), low cardiac output and resistance to medical therapy. This study aimed to estimate post-operative CVP in TCPC patients (CVPTCPC) using data routinely collected during pre-operative assessment. We sought to determine if this metric correlated with measured post-operative CVP and if it was associated with EFF. Methods In this retrospective study, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For example, Chen et al found in a meta-analysis that a higher CVP value was associated with higher mortality (odds ratio [OR] 1.65) and a greater risk of AKI (OR, 2.09). Quail et al found that a higher CVP is associated with a higher risk of early Fontan failure after total cavopulmonary connections [10]. Liu et al also found that a controlled lower CVP could reduce blood loss during hepatectomy and recommended the promotion of CVP use in clinical settings [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chen et al found in a meta-analysis that a higher CVP value was associated with higher mortality (odds ratio [OR] 1.65) and a greater risk of AKI (OR, 2.09). Quail et al found that a higher CVP is associated with a higher risk of early Fontan failure after total cavopulmonary connections [10]. Liu et al also found that a controlled lower CVP could reduce blood loss during hepatectomy and recommended the promotion of CVP use in clinical settings [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies have reported that higher CVP values may be associated with patients' poor outcomes in different conditions, such as patients undergoing cardiac surgery [11], early Fontan failure [10], acute kidney injury (AKI) [8,9], patients undergoing cardiopulmonary bypass surgery [9], and critically ill patients [2]. A controlled lower CVP can also reduce blood loss during hepatectomy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Manan H. Desai, MD, and Can Yerebakan, MD Approximately 5 decades ago, Fontan and colleagues 1 gave a new lease on life to patients with single ventricle physiology by introducing a novel surgical procedure. Soon after the total cavopulmonary connection (TCPC) surgery was designed, it was realized that patient selection was critical for the success of the procedure; thus, the commandments of the Fontan procedure were introduced.…”
Section: Commentary: If Only We Knew When We Would Failmentioning
confidence: 99%
“…We congratulate Quail and colleagues 1 for their article in this issue of the Journal and their efforts to advance this complex field of single-ventricle palliation. Currently, the Fontan procedure, or total cavopulmonary connection (TCPC), serves as the last step of palliation for several single-ventricle congenital heart conditions.…”
mentioning
confidence: 99%